Analysis of the Influence of Eccentricity Error of Gear Skiving Cutting Tool Movement on Gear Skiving Accuracy - Guo Wenchao; Yang Yu; Mao Shimin; Guo Zheng (Jixie chuandong)
The skiving cutting tool movement eccentricity error has obvious influences on skiving gear accuracy. Based on the theoretical and experimental study of skiving，the influences of cutting tool eccentricity error on the helix deviations and the tooth profile deviations of the workpiece machined by skiving and action mechanism are investigated. Firstly，experiments of skiving process method are carried out，which are focused on the skiving waves on the tooth flanks of the workpieces，it is found that the amplitude of the waves can be decreased by reducing the tool eccentricity error. Then，based on the experiment study，the theoretical analysis of the influences of tool eccentricity error on the helix deviations and the tooth profile deviations of the workpiece are carried out，and the wave generation mechanisms and periodic characteristic are investigated. Finally，based on the experiments and theoretical study，the design method of number of tooth of skiving cutting tool，which can be used to improve the gear skiving waves on the tooth surface of the workpieces is proposed.